Effects of healthy eating patterns based nutrition education and providing structured suplementary feeding on improving the nutritional status of stunted children - Mahfuzhoh Fadillah Heryanda; Nur Khoiriyah (AcTion: Aceh Nutrition Journal, 2024)
Nutrition education can improve mothers' knowledge in fulfilling nutritional needs among children under five years through provision of supplementary feeding. Local ingredients based supplementary feeding which had high nutritional value can contribute to improving the nutritional status of children. The aim of this study was to analyze the effect of healthy eating patterns nutritional education and provision of supplementary feeding on improving the nutritional status of stunted children under five years. This study used a quasi-experimental design with a pre-posttest with control group design carried out in Sidawangi Village in August-October 2023. The subjects were children under five years and their mothers (10 intervention group: 10 control group). The interventions were nutritional education and supplementary feeding for a month. Nutritional knowledge data was obtained from interviews using a questionnaire, and nutritional status data (Height-for-Age) was obtained based on z-score calculations. Data was analyzed using Wilxocon, Mann-Whitney, and independent t-test.  The average difference in HAZ index in the intervention group (z-score: 0,81 SD) compared to the control group (z-score: -0,50 SD). There was a significant difference between the average difference in the HAZ index in the intervention group and the control group (p=0,001). Nutrition education improved nutritional knowledge of mothers in understanding nutrition education and supplementary feeding (p=0,042). In conclusion, nutritional education intervention can improve the nutritional knowledge of mothers and supplementary feeding can improve the nutritional status of children.